2016
DOI: 10.3389/fmicb.2016.00035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Amino Acid Residues Modulating Intracellular and In vitro Microcin E492 Amyloid Formation

Abstract: Microcin E492 (MccE492) is a pore-forming bacteriocin produced and exported by Klebsiella pneumoniae RYC492. Besides its antibacterial activity, excreted MccE492 can form amyloid fibrils in vivo as well as in vitro. It has been proposed that bacterial amyloids can be functional playing a biological role, and in the particular case of MccE492 it would control the antibacterial activity. MccE492 amyloid fibril’s morphology and formation kinetics in vitro have been well-characterized, however, it is not known whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…These short peptides could self-assemble into typical amyloid fibrils on their own and played determinative roles for the amyloidogenic property of their full-length versions. [12][13][14][15][16][17][18][19] On the other hand, some de novo designed short peptides have also shown the ability to form amyloid fibrils, providing useful models for investigating the molecular basis of this intriguing process. [20][21][22][23][24][25] Although these peptides were still quite different from each other considering their exact amino acid sequences, a large proportion of them showed a common feature of amphiphilic structure, suggesting the essential role of hydrophobic interaction in the formation of amyloid fibrils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These short peptides could self-assemble into typical amyloid fibrils on their own and played determinative roles for the amyloidogenic property of their full-length versions. [12][13][14][15][16][17][18][19] On the other hand, some de novo designed short peptides have also shown the ability to form amyloid fibrils, providing useful models for investigating the molecular basis of this intriguing process. [20][21][22][23][24][25] Although these peptides were still quite different from each other considering their exact amino acid sequences, a large proportion of them showed a common feature of amphiphilic structure, suggesting the essential role of hydrophobic interaction in the formation of amyloid fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Although these peptides were still quite different from each other considering their exact amino acid sequences, a large proportion of them showed a common feature of amphiphilic structure, suggesting the essential role of hydrophobic interaction in the formation of amyloid fibrils. [26][27][28][29][30] Among all these amyloid-like peptides, Aβ [16][17][18][19][20][21][22] with the sequence of KLVFFAE might be the most widely studied one. 31 A lot of work have been done on this peptide, but its bolaamphiphilic feature, ie, 2 hydrophilic heads connected by a hydrophobic section, has not received enough attention.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli BL21 DE3 cells were transformed with the pMccE492 plasmid carrying a 13-kbp segment of the microcin E492 production cluster, originally cloned from Klebsiella pneumoniae RYC492 (Aguilera et al, 2016). An overnight culture of these cells grown in LB broth (10 g/L tryptone, 10 g/L NaCl and 5 g/L yeast extract) were typically used to inoculate (1:1000) 2 L of M9 medium supplemented with citrate and glucose (2 g/L each) and ampicillin (100 µg/mL).…”
Section: Microcin E492 Purificationmentioning
confidence: 99%
“…The gene cluster encoding for active MccE492 is located in the genomic island GI-E492 (Marcoleta et al, 2013b(Marcoleta et al, , 2016, which was found to be highly prevalent among liver abscessassociated strains of K. pneumoniae (Marcoleta et al, 2016(Marcoleta et al, , 2018Lam et al, 2018). A striking characteristic of MccE492 is that it forms amyloid fibers both in vivo and in vitro ( Figure 1A; Bieler et al, 2005;Arranz et al, 2012;Marcoleta et al, 2013a;Aguilera et al, 2016). Regarding its cytotoxic activity, MccE492 was toxic to different malignant cell lines (HeLa, Jurkat, and RJ2.25), and did not have effect on KG-1 and a primary culture from human tonsils (Hetz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these functional amyloids have been widely reported in different organisms, including bacteria. In prokaryotes, diverse functions have been described for these amyloids, such as a role in biofilm development [11], formation of curli and pili [12], or creation of pores in the host membrane [13]. In this chapter we intend to provide a guideline to develop approaches that can be used to detect the fibers of sRNA protein cofactors, precisely molecular imaging, such as atomic force microscopy and transmission electron microscopy, infrared spectroscopy, synchrotron radiation circular dichroism, and small angle X-ray scattering.…”
Section: Introductionmentioning
confidence: 99%